Italy beyond Gomorrah : Roberto Saviano and transmedia disruption - Bernardi, Floriana (Rowman & Littlefield Publishers, 2017)
When Roberto Saviano published Gomorrah in 2006 he exposed the Camorra, an organized crime network with global reach emanating from Naples. This ground-breaking work became an international best seller, inspired a film, and a new TV series. The author received so many death threats from the Camorra that he remains under police protection. Italy beyond Gomorrah investigates the conditions and modalities by which the huge media phenomenon developed around Roberto Saviano after the publication of Gomorrah and the ways in which this has engendered a political discourse starting from his 'denuncia' of the mechanisms of the modern mafia and its bosses. Focusing on Saviano's disruptive work and the representation of his 'charismatic body', redefining the figure and task of the modern intellectual, the book stresses the agency of literature and the relevance of the internet and major social networks in the creation of networks of subjectivities and establishing ethical-political duties which are grounded in a 'passional communication' between the writer and his audience, as well as on a micropolitics of affects. Through the interpretation of Saviano's work it also provides provide a cross sectional insight into Italy in the post-Berlusconi age